(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s ((3eMeO Hf eMeO GHf YeQhf s)
(3ChdgG (B:s
(3HeGOI YLO s
(3BNQgG (B:s
(3HeGOI YOK s
(3GdehLhO efgG (B16 (3LRAs
(3ecJhH Ydi BNQ CcKQ CLRGFgG (B"(3HdZ ebGHdI HGdCUd GdecJhH HMSH GdWGbI hddg GdMeO(B"s
(3HQSe NRGfI Gdedc GdeDjO TjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B318 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B515s
Keywords: (3GddZIs